2021
DOI: 10.3390/su132111968
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Mouth-Generated Aerosols in a Modularly Constructed Hospital Room

Abstract: Modular construction methods have been widely used in the civil engineering industry due to ease of assembly, the convenience of design, and allowing for flexibility in placement while making the construction more sustainable. With the increasing number of COVID-19 cases, the capacity of the hospital is decreasing as more intensive care units (ICU) are allocated to COVID-19 cases. This limited capacity can be addressed by using modular construction to provide field hospitals. This paper adopts transient Lagran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Ventilation is a critical engineering solution to minimize the infection risk in the indoor environment. Many researchers have suggested that increasing the amount of fresh air given to the buildings from the ventilation systems decreases the infection risk in buildings [8][9][10][11]. Since the early 2000s, there has been an increase in studies examining the effect of indoor ventilation on airborne transmission.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ventilation is a critical engineering solution to minimize the infection risk in the indoor environment. Many researchers have suggested that increasing the amount of fresh air given to the buildings from the ventilation systems decreases the infection risk in buildings [8][9][10][11]. Since the early 2000s, there has been an increase in studies examining the effect of indoor ventilation on airborne transmission.…”
Section: Introductionmentioning
confidence: 99%
“…With the 2002-2003 SARS virus epidemic, the focus on this area increased, and with the pandemic that occurred in 2019, studies in this area have diversified significantly. In addition to different interior spaces such as classrooms [12,13], offices [14,15], restaurants [9], hospital rooms [8,16], ophthalmology clinics [17], dental clinics [18], and aircraft [19][20][21], bus [22,23] and train cabins [24,25], different topics such as exposure type and severity [26], and social distance [27,28] have been studied by many researchers. Most of the studies are parametric, and it is aimed to find a scenario that will minimize the risk of contamination according to the title examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation